Beyond Search: A Technology Probe Investigation - Sellen, Abigail; Harper, Richard (Web Search Engine Research, 2012)
Purpose — We assert that researchers developing new web interaction tools should consider an array of user motives beyond query-based information retrieval. This chapter reports on two probes used to investigate user activities that go beyond search as traditionally conceived. Design/methodology — This chapter reviews research on user experiences with search engines and general web use. It then describes the design and case study of cards and pebbles, two search engine- AU :1 based probes developed to help elicit new concepts for web-based experiences. Findings — Participants reflect on their experiences with the probes and offer ideas regarding how to incrementally shift the traditional search paradigm and conceive of the web in new ways. Implications/value — This investigation serves as a starting point by offering criteria that should be considered when designing new ‘beyond search’ tools.